An Industrial systems design study on Jenny's Garments, Inc. - Deguito, Therese Sheila; Sabando, Luche; Valenzuela, Maria Sarah (Diliman, Quezon City College of Engineering, 2001)
The supply chain, briefly defined, is how organizations are linked to each other, from the suppliers, the manufacturer and down to the end users. Its goal is being able to reduce the uncertainty risks in the chain making the inventory levels, cycle time, processes, and the end-customer service level at its optimum. This paper will look into the entire system of Jenny's Garments, Inc., a garment exporter located in Pasig City, on how it manages its supply chain and how it can be improved. The proponents documented the system from the inbound activities, the manufacturing as well as the outbound activities. The system was analyzed using the streamline analysis and Ishikawa Diagram; the following major problems were detected: lax supplier performance, stock retrieval difficulty in the warehouses, production quality, and driver attitude. Alternative solutions were generated and then evaluated against the must and want objectives. Solutions to the problems include the periodic monitoring of suppliers, putting up of an International Purchasing Office, and the implementation of quality at the source. The best solution was provided with a potential problem analysis. The proponents also presented an implementation strategy for each recommendation made.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Jenny's Garments, Inc; Marketing channels--Management.; Delivery of goods--Management.; Physical distribution of goods--Management.; Customer services--Management.; Industrial procurement; Materials management; System design